Religious participation is associated with increases in religious social support in a national longitudinal study of African Americans - Le, Daisy (J Relig Health, 2016)
OBJECTIVE: This study reports on the association between religious beliefs and behaviors and the change in both general and religious social support using two waves of data from a national sample of African Americans. DESIGN: The Religion and Health in African Americans (RHIAA) study is a longitudinal telephone survey designed to examine relationships between various aspects of religious involvement and psychosocial factors over time. PARTICIPANTS: RHIAA participants were 3,173 African American men (1,281) and women (1,892). A total of 1,251 men (456) and women (795) participated in wave 2 of data collection. RESULTS: Baseline religious behaviors were associated with increased overall religious social support from baseline to wave 2 (p<.001) and with increased religious social support from baseline to wave 2 in each of the following religious social support subscales: emotional support received (p<.001), emotional support provided (p<.001), negative interaction (p<.001), and anticipated support (p<.001). Religious beliefs did not predict change in any type of support, and neither beliefs nor behaviors predicted change in general social support. CONCLUSIONS: African Americans who are active in faith communities showed increases in all types of religious social support, even the negative aspects, over a relatively modest longitudinal study period. This illustrates the strength of the church as a social network and the role that it plays in people’s lives.